The Influence of Middle School Students' Self-Efficacy on AS Murabbi's Religion Teacher Education - Haryanto, Sri (LPPM Undiksha, 2024)
The low level of teacher self-efficacy in Islamic religious education in secondary schools is increasing. It is important to understand the influence of self-efficacy on teaching quality, which contributes to educational progress. This is urgent to study because there are differences between theory, expectations and reality in the field, so the aim of this research is to analyze and identify the level of quality of Islamic religious education (PAI) teachers and determine the relationship between the self and the teacher. -efficacy and quality of teaching. The research method used is a quantitative survey method with a descriptive and inferential approach. The research sample consisted of 540 respondents from a population of 5000 PAI teachers. The data collection technique was carried out through a validated questionnaire, using a Likert scale of 1 to 5 points. The data analysis technique used descriptive statistics with the help of SPSS version 25.0 to calculate the mean, percentage and standard deviation. The research results showed that the average self-efficacy and teaching quality were 4.32 respectively. The findings show a simple positive correlation between self-efficacy and teaching quality, with the influence of self-efficacy on variations in teaching quality of 34.2%. In conclusion, increasing teacher self-confidence can improve the quality of Islamic Religious Education teaching. The implications of this research are important for the development of teacher training models and teaching practices. Suggestions for further research are to explore other factors that can influence the quality of teaching and conduct longitudinal research to see changes over time.